The Reform of China's Energy Policies - Joachim Betz (German Institute of Global and Area Studies (GIGA), 2013)
China's shift in energy policies has been broader, deeper and more successful than that of most other emerging economies, although the economic costs of this transition are tremendous because China is an over-industrialized country whose production is highly energy-intense and it depends on emission-intensive coal as main energy source. Factors that have influenced energy reforms, which focus on saving and conserving energy, developing renewable sources and nuclear power, are - on the international level - the impact of climate change on India, the desire to be recognized as a responsible power in the international community, China's dangerously growing dependence on energy imports, and the uncertain prospects of equity oil abroad for energy security. Domestic factors are the growing assertiveness of environmental NGOs, relatively effective sectorial governance, and the embedding of energy policies in a blueprint for industrial upgrading.
Keywords: 300; energy policy; climate change; energy institutions; international climate summits; political system; civil society